Definitive Chemoradiation With Full-dose Gemcitabine for Unresectable Pancreatic Cancer: Efficacy of Involved-Field Radiotherapy. (October 2017) - Zhou, Jessica; Fang, Charles X.; Shen, Jincheng; Schipper, Matthew J.; Zalupski, Mark M.; Minter, Rebecca M.; Simeone, Diane M.; Hart, Deanna; Eagle, Taylor; Kimmel, Grace W.; Vainshtein, Jeffrey; Lawrence, Theodore S.; et al.
Abstract : Objectives: Definitive chemoradiotherapy for unresectable pancreatic cancer has traditionally involved 5-fluorouracil-based chemotherapy. Our institution has a long history of combining gemcitabine and radiotherapy (RT), and performed a retrospective review of all patients treated in this manner. Materials and Methods: We reviewed the records of 180 patients treated from 1999 to 2012. Mean RT dose was 40.9 Gy in 2.2-Gy fractions, and targeted only radiographically apparent disease. Ninety-six percent of patients received full-dose gemcitabine-based chemotherapy with RT. Kaplan-Meier was used to analyze time-to-event endpoints, and Cox regression models were used to assess significant prognostic variables. Results: Eighty-nine percent of patients completed RT without a toxicity-related treatment break. Median follow-up was 10.2 months. Twenty-nine percent of patients had a radiographic decrease in primary tumor size following treatment. Median overall survival was 11.8 months, time to distant metastasis (TDM) was 6.7 months, and time to local recurrence (TLR) was 8.3 months. On multivariate analysis, male sex, lower performance status, and higher posttreatment CA 19-9 level predicted for worse overall survival. Posttreatment, CA 19-9 was also associated with TDM and TLR, and radiographic tumor response was associated with better TLR. Conclusion: Definitive chemoradiation using full-dose gemcitabine is well tolerated and achieves survival outcomes comparable to reported trials in the literature.